2021
DOI: 10.1029/2021gl094543
|View full text |Cite
|
Sign up to set email alerts
|

Preservation and Destruction of Holocene Marine Terraces: The Effects of Episodic Versus Gradual Relative Sea Level Change

Abstract: Holocene marine terraces occur globally and record information about the timing and magnitude of past coseismic events. Staircased terraces develop through repetitive coseismic uplift of shore platforms, but are also subject to destruction from subsequent wave erosion and rock weathering. In this study we calibrate a rock coast evolution model using terrace field data from Mahia Peninsula, New Zealand, and use it to investigate how relative sea level (RSL) change influences Holocene terrace development. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The model integrates (i) our current understanding of shore platform development processes from the rock coast literature, (ii) insights from numerical modelling studies of Holocene terrace development (e.g. Matsumoto et al, 2021), and (iii) our observations of downwear and backwear erosion rates recorded at the initial and penultimate stages of terrace formation at Kaik oura and M ahia. The MEM downwear data from Kaik oura provides new insights into the narrow window of time between uplift and vegetation and cover-bed development, whereas the backwear data from M ahia characterizes the final stages of marine terrace truncation.…”
Section: Discussionmentioning
confidence: 94%
“…The model integrates (i) our current understanding of shore platform development processes from the rock coast literature, (ii) insights from numerical modelling studies of Holocene terrace development (e.g. Matsumoto et al, 2021), and (iii) our observations of downwear and backwear erosion rates recorded at the initial and penultimate stages of terrace formation at Kaik oura and M ahia. The MEM downwear data from Kaik oura provides new insights into the narrow window of time between uplift and vegetation and cover-bed development, whereas the backwear data from M ahia characterizes the final stages of marine terrace truncation.…”
Section: Discussionmentioning
confidence: 94%
“…The formation of marine terraces from Holocene co‐seismic uplift, their longevity in the contemporary environment, and vulnerability to denudation provides insight into the potential of such landforms to act as records of Holocene palaeo‐earthquakes (Litchfield et al, 2020; Pedoja et al, 2014). However, within suites of marine terraces, there may be ‘missing’ terraces (Dickson et al, 2022; Howell & Clark, 2022; Litchfield et al, 2020; Matsumoto et al, 2021). Combining the model of wetting and drying cycles with observations of erosion rates on the platform at Kaikōura, it is evident that contemporary processes are relevant to elucidating landform preservation and determining if post‐uplift changes in wetting and drying cycles can remove incipient marine terraces.…”
Section: Discussionmentioning
confidence: 99%
“…Recent numerical modelling by Matsumoto et al (2021) has suggested that a marine terrace formed during earthquake uplift might be more likely to be preserved if the preceding earthquake uplift event was smaller than the tidal range of the coastline. This non‐intuitive result arises in their model because downwearing of a shore platform that has been uplifted only a small amount allows it to be unified with the newly uplifted seafloor, creating an expansive shore platform that is more likely to be preserved as a terrace when it is next uplifted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations